Non-alcoholic fatty liver disease: pathogenesis and assessing the impact of dietary bioactive compounds on the liver - OĞUZ, ESMA (My University, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a pathological condition ranging from simple steatosis to non-alcoholic steatohepatitis, cirrhosis, and liver cancer. NAFLD is a complex disease mediated by metabolic, environmental, and genetic mechanisms. Many factors such as insulin resistance, lipotoxicity, inflammation, mitochondrial dysfunction, endoplasmic reticulum stress, circadian rhythm, genetics, epigenetics, dietary factors, and gut microbiota play a crucial role in the pathogenesis of NAFLD. Lifestyle changes such as healthy diet, physical activity, avoiding alcohol and smoking are involved in the NAFLD treatment. Dietary bioactive compounds including curcumin, resveratrol, catechins, quercetin, sulforaphane, epigallocatechin-3-gallate, alkaloids, vitamins, and peptides have many health promoting effects such as antioxidant, anti-inflammatory, antihypertensive, chemopreventive, and hepatoprotective. In this review, the pathophysiology of NAFLD and the effects of dietary bioactive compounds on this disease will be discussed in detail with updated information.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Dietary Bioactive Compounds; Non-Alcoholic Fatty Liver Disease; Pathogenesis; Dietary Bioactive Compounds